The physics of elementary particles - Muirhead, H. (Hugh) (Pergamon Press, 1965)
The Physics of Elementary Particles details the physical principles that govern the behavior of elementary particles. The title focuses on discussing the theoretical concepts of elementary particles. The text first tackles the discovery and classification of the elementary particles, and then proceeds to covering the intrinsic properties of the particles. Chapter 3 talks about the preliminaries to a quantized field theory, while Chapter 4 deals with the quantum theory of non-interacting fields. Next, the selection details the symmetry properties of free fields. The next five chapters are dedic.